High-resolution study of Middle Palaeolithic deposits and formation processes at Tabun Cave, Israel: Guano-rich cave deposits and detailed stratigraphic appreciation of Layer C. (15th December 2021) - Friesem, David E.; Shahack-Gross, Ruth; Weinstein-Evron, Mina; Teutsch, Nadya; Weissbrod, Lior; Shimelmitz, Ron
Abstract: The hominin-bearing Middle Palaeolithic [MP] Layer C of Tabun Cave, Mount Carmel, Israel, has been extensively studied for over 90 years, but many questions about its chronology, the identity of its hominin remains and the nature of its formation remain open. Tabun Layer C, part of the 13-m thick MP deposits at the cave, presents a complex sedimentary sequence composed of multiple beds and thinner laminae within them (<5 cm thick), varying in colour, texture, and the amount of associated remains from human activity. In this study, we re-sampled, in higher resolution than any previous study, the sediments exposed along the full stratigraphic sequence of Layer C (⁓2.5 m thick), including the deposits immediately below and above it. The studied sequence largely conforms to the three Major Sedimentological Units (MSU I-III, themselves analogous to Garrod's layers B-D) previously defined by Jelinek et al. (1973). Using state-of-the-art micro-stratigraphic and micro-geoarchaeological approach and methods we examined the deposits within MSU II and those associated with the transitions between MSU III–II and between MSU II–I. The results demonstrate that the beds and laminae of MSU II (Garrod's Layer C) are primarily composed of bat and bird guano at various stages of preservation, occurring with varying amounts of allochthonous terra rossa and human activity remains, and generally not showing severe diagenetic changes. Significantly, this study allowed us to identify four depositional sub-units in MSU II, each composed of tens to hundreds of cm-to mm-thick laminae. An abrupt change from slow to rapid deposition of guano occurs between MSU III and MSU IId, followed by intensive use of fire in MSU IIc, then intermittent hominin use of the cave in MSU IIb. Lowered anthropogenic use of the cave characterises the upper part of the section, where deposits become primarily biogenic (MSU IIa) and geogenic (MSU I). Our identification of large amounts of guano further contributes towards more informed research of the Levantine MP in cave sites. We demonstrate that attention to components within guano deposits can allow distinguishing among different guano producers (e.g., bats and birds), and that it may form a sounder basis for reconstructing changing environments at both regional and local scales, as well as human–environment relations. Graphical abstract: Image 1 Highlights: High-resolution geoarchaeological study of Layer C (MSU II) at Tabun Cave. Identification of tens to hundreds of mm-cm thick laminae in each sediment bed. The major source of material is bat and bird guano alongside reworked terra rossa. Division of MSU II to four sub-units and precise stratigraphic position of its beginning and end. New insights into the site's formation processes and the interplay between human action and animal activity.